THE USE OF SAND PAPER LETTERS IN TEACHING THE ENGLISH ALPHABET - Ivy, Casupanan; Rodolfo, Casupanan (PUPIL: International Journal of Teaching, Education and Learning, 2018)
This study was conducted as part of the curriculum monitoring program to determine the level of student performance in English, specifically on letter recognition of Royal International School, 2nd Semester, SY 2014-2015.The experimental method was utilized using the Pre Test and Post Test Equivalent Group Design where the lowest performing class was the focus of the study of preschool department. The study involved a total of fourteen (14) students randomly selected from the kindergarten class. Seven (7) samples were identified as control group and seven (7) as experimental group using fish bowl technique to avoid bias, each with an equal chance of being selected. The researcher made sure that both groups were almost identical based on their Pre-Test results, and parameter such as the means were taken into consideration. Findings showed that the use of Sand Paper Letters in the experimental group has a significant effect on student performance.